Biofortification of sweet corn hybrids for provitamin-A, lysine and tryptophan using molecular breeding. (November 2020) - Mehta, Brijesh K.; Muthusamy, Vignesh; Zunjare, Rajkumar U.; Baveja, Aanchal; Chauhan, Hema S.; Chhabra, Rashmi; Singh, Ashok K.; Hossain, Firoz
Abstract: Traditional sweet corn is poor in provitamin-A, lysine and tryptophan, deficiency of which causes serious health problems. Here, parental lines of two shrunken2 ( sh2 ) -based sweet corn hybrids viz., ASKH-1 and ASKH-2 were targeted for introgression of crtRB1 and opaque2 ( o2 ) genes through marker-assisted backcross breeding. Gene-based markers; umc1066 (SSR) and 3′TE-InDel were utilized for foreground selection of o2 and crtRB1, respectively in BC1 F1, BC2 F1 and BC2 F2 generations. Background selection employing 102–113 polymorphic SSRs led to >90% recovery of recurrent parent genome. Reconstituted hybrids recorded high mean provitamin-A (18.98 μg/g) with a maximum of 7.7-fold increase over original hybrids (3.12 μg/g). High mean lysine (0.39%) and tryptophan (0.10%) with an average enhancement of 1.71- and 1.79-fold, respectively was recorded among reconstituted hybrids over original versions (lysine: 0.23%, tryptophan: 0.06%). Improved hybrids exhibited high phenotypic resemblance with their original hybrids. The average cob yield (11.82 t/ha) and brix (17.66%) of improved hybrids was at par with their original versions (cob yield: 11.27 t/ha, brix: 17.04%). These biofortified sweet corn hybrids rich in provitamin-A, lysine and tryptophan hold immense significance as multinutrient-rich balanced food. This is the first report to stack sh2, crtRB1 and o2 genes to improve nutritional quality in sweet corn. Graphical abstract: Image 1 Highlights: Traditional sweet corn lacks adequate provitamin-A, lysine and tryptophan. Two sweet corn hybrids were biofortified by introgression of o2 and crtRB1 genes. Improved hybrids possessed significantly high provitamin-A, lysine and tryptophan. Biofortified sweet corn hybrids would provide multinutrient-rich balanced food. This is the first report of stacking o2 and crtRB1 genes in sweet corn.